POLA WIRAUSAHA MAHASISWA MANAJEMEN DAKWAH DALAM MENJALANKAN KEGIATAN ENTREPRENEUR (MEMPELAJARI TEKNIK DAN STRATEGI PEMASARAN PRODAK KOPERASI): Analisis Pengembangan Kewirausahaan Mahasiswa Berbasis Koperasi - Nurman Tsalis; Idah Jubaedah; Imam Aji Pratomo; Sobirin (STKIP Subang, 2025)
This study aims to analyze the entrepreneurial patterns of Islamic Da'wah Management students in managing cooperatives as a medium for entrepreneurship learning and da'wah bil hal. The students are not only oriented toward economic profit but also integrate Islamic ethical values, creativity, social responsibility, and digital marketing strategies to enhance the competitiveness of cooperative products. This research employs a qualitative method using library research, reviewing books, scientific journals, research reports, and academic documents relevant to student entrepreneurship, cooperative management, and da'wah bil hal. By applying the Business Entrepreneur, Social Entrepreneur, and Academic Entrepreneur models simultaneously, students are able to develop entrepreneurial patterns that combine business, social, and academic orientations. The analysis of the 4P marketing mix, the STP approach (Segmenting, Targeting, Positioning), and SWOT analysis indicates that student cooperatives have strong potential for growth despite facing challenges such as limited capital, low digital marketing literacy, and increasing market competition. The findings confirm that cooperatives serve as a strategic entrepreneurial laboratory for Da'wah Management students in building economic independence grounded in Islamic da'wah values.